Thyroid cancer patient perceptions of radioactive iodine treatment choice: Follow‐up from a decision‐aid randomized trial. Issue 20 (20th July 2015) - Sawka, Anna M.; Straus, Sharon; Rodin, Gary; Heus, Lineke; Brierley, James D.; Tsang, Richard W.; Rotstein, Lorne; Ezzat, Shereen; Segal, Phillip; Gafni, Amiram; Thorpe, Kevin E.; Goldstein, David P.
<x xml:space="preserve">Abstract</x> BACKGROUND Patient decision aids (P‐DAs) inform medical decision making, but longer term effects are unknown. This article describes extended follow‐up from a thyroid cancer treatment P‐DA trial. METHODS In this single‐center, parallel‐design randomized controlled trial conducted at a Canadian tertiary/quaternary care center, early‐stage thyroid cancer patients from a P‐DA trial were contacted 15 to 23 months after randomization/radioactive iodine (RAI) decision making to evaluate longer term outcomes. It was previously reported that the use of the computerized P‐DA in thyroid cancer patients considering postsurgical RAI treatment significantly improved medical knowledge in comparison with usual care alone. The P‐DA and control groups were compared for the following outcomes: feeling informed about the RAI treatment choice, decision satisfaction, decision regret, cancer‐related worry, and physician trust. In a subgroup of 20 participants, in‐depth interviews were conducted for a qualitative analysis. RESULTS Ninety‐five percent (70 of 74) of the original population enrolled in follow‐up at a mean of 17.1 months after randomization. P‐DA users perceived themselves to be significantly more 1) informed about the treatment choice (P = .008), 2) aware of options (P = .009), 3) knowledgeable about treatment benefits (P = .020), and 4) knowledgeable about treatment risks/side effects (P = .001) in comparison with controls. There were no significant group differences in decision satisfaction (P = .142), decision regret (P = .199), cancer‐related worry (P = .645), mood (P = .211), or physician trust (P = .764). In the qualitative analysis, the P‐DA was perceived to have increased patient knowledge and confidence in decision making. CONCLUSIONS The P‐DA improved cancer survivors' actual and long‐term perceived medical knowledge with no adverse effects. More research on the long‐term outcomes of P‐DA use is needed. Cancer 2015;121:3717–3726. © 2015 American Cancer Society.